VD_FINDINFO Arrêt / 2016 / 214 vom 3. März 2016 - VD Tribunal cantonal (2016)
ASSURANCE POUR SOINS DENTAIRES, AM, ASSURANCE-MALADIE PRIVÉE | 25 al. 1 LAMal, 31 al. 1 let. c LAMal, 33 al. 2 LAMal, 33 al. 5 LAMal, 33 let. d OAMal, 19a OPAS